2022
DOI: 10.1186/s43054-021-00093-9
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal parasitic infection among school children in Dakahlia governorate, Egypt: a cross-sectional study

Abstract: Background Intestinal parasitic infections are still representing a significant health problem in developing countries including Egypt. School children are highly vulnerable to this type of infection, and they suffered many health consequences. This study was conducted to identify the prevalence of intestinal parasitic infection among school children and its related factors. Results This is a school-based cross-sectional study conducted on 726 scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…For example, a cross-sectional study in Egypt conducted between October 2020 and January 2021, reported a higher prevalence of G. lamblia (8.5%) and of E. histolytica (12.3%) in school children selected in primary and secondary schools. Researchers in Egypt explained this high prevalence of bad environmental sanitary conditions and decreased levels of personal hygiene and awareness in their country [15]. In Yemen, a study also in children showed a very high prevalence for both E. histolytica (61.7%) and G. lamblia (23.94%).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a cross-sectional study in Egypt conducted between October 2020 and January 2021, reported a higher prevalence of G. lamblia (8.5%) and of E. histolytica (12.3%) in school children selected in primary and secondary schools. Researchers in Egypt explained this high prevalence of bad environmental sanitary conditions and decreased levels of personal hygiene and awareness in their country [15]. In Yemen, a study also in children showed a very high prevalence for both E. histolytica (61.7%) and G. lamblia (23.94%).…”
Section: Discussionmentioning
confidence: 99%
“…This study determined the prevalence of intestinal parasitic infection among a cohort of Egyptians, in addition to investigating mono- and poly-parasitic patterns with their associated risk factors. Epidemiological studies are essential for determining the prevalence of intestinal parasitic infections, identifying risk factors, and creating effective prevention and control strategies, all of which continue to be a major health concern in developing countries such as Egypt 19 .…”
Section: Discussionmentioning
confidence: 99%
“…There was a relatively high prevalence of intestinal parasites (59.6%) in the studied cohort of Egyptians which was similar to a study by Omar and Abdelal 20 , who reported a 56% prevalence of intestinal parasitic infection among Egyptian patients. Ahmed and Abu-Sheishaa 19 reported that IPs represented an overall prevalence of 32.9% among school children. This variation in findings may be due to differences in sociodemographic and environmental factors with different exposures to risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant developments in sanitation and hygiene in Egypt, IPI remains a public health problem that differs in their intensity among various Egyptian governorates. The prevalence of IPI among school children in Dakahlia governorate was 32.9% (Ahmed and Abu-Sheishaa, 2022). In Cairo, approximately 51% of patients with gastrointestinal symptoms were positive for IPI (Hussein et al 2017).…”
Section: Diarrhoealmentioning
confidence: 98%